2005
DOI: 10.1103/physrevb.71.035336
|View full text |Cite
|
Sign up to set email alerts
|

Level structure and spin-orbit effects in quasi-one-dimensional semiconductor nanostructures

Abstract: We investigate theoretically how the spin-orbit Dresselhaus and Rashba effects influence the electronic structure of quasi-one-dimensional semiconductor quantum dots, similar to those that can be formed inside semiconductor nanorods. We calculate electronic energy levels, eigen-functions, and effective g-factors for coupled, double dots made out of different materials, especially GaAs and InSb. We show that by choosing the form of the lateral confinement, the contributions of the Dresselhaus and Rashba terms c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…29 Motivated by this earlier proposal and its potential impact on semiconductor spintronics, many researchers are actively investigating spin-orbitrelated physics in a variety of semiconductor nanostructures. 30,31,[34][35][36][37][38][39][40][41][42][43][44][45] Here we extend our previous investigation on the coherent SO control of entangled and spin-polarized electrons and their shot noise for transport in a beam-splitter configuration ͑Fig. 1͒ with local spin-orbit interactions, i.e., interactions acting within only a finite region of one of the two onedimensional incoming leads.…”
Section: Introductionsupporting
confidence: 56%
“…29 Motivated by this earlier proposal and its potential impact on semiconductor spintronics, many researchers are actively investigating spin-orbitrelated physics in a variety of semiconductor nanostructures. 30,31,[34][35][36][37][38][39][40][41][42][43][44][45] Here we extend our previous investigation on the coherent SO control of entangled and spin-polarized electrons and their shot noise for transport in a beam-splitter configuration ͑Fig. 1͒ with local spin-orbit interactions, i.e., interactions acting within only a finite region of one of the two onedimensional incoming leads.…”
Section: Introductionsupporting
confidence: 56%
“…The nanorod width ͑cross section͒ is roughly ten times smaller than the dots' length. Introducing a weak magnetic field in the z direction that breaks the spin degeneracy ͑but produces no significant diamagnetic shift͒, the Hamiltonian takes the form 35,37,38 …”
Section: Quantum Dot System and Relaxation Ratesmentioning
confidence: 99%
“…[30][31][32][33][34] We have recently studied the electronic states of such quasi-1D double dots, and analyzed their spinmixed character, which arises from the spin-orbit ͑SO͒ interaction. 35 An interesting and potentially useful characteristic of these QD structures is that they can be designed so that only the Rashba or the Dresselhaus spin-orbit couplings are present in a given structure. 35 Therefore, they lend themselves ideally to the experimental study of the individual spin-orbit couplings, which is a desirable feature in quantum dot systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the average values of @ q V q are in the order of meV/Å [25]. Taking into account the values of g R for different semiconductors, the value of a q can vary in the range of a few meVnm to a few tens meVnm in low dimensional systems [25][26][27].…”
Section: Modelingmentioning
confidence: 99%